The role of advance directives regarding the patient's consent. Views held by the first Spanish Act regulating the patient's autonomy and differences with the Common Law tradition. (December 2013) - Rodriguez-Vazquez, Virgilio
The present article aims at examining the legal value of advance directives in those cases where a patient cannot state his/her consent due to his/her being in a state of unconsciousness or temporary disability. In order to reach a conclusion about the issue at hand, I analyse Act 41/2002, 14 November, which regulates the patient's autonomy in Spain. I then compare Act 41/2002 to some other legal documents that deal with this question, both in and outside Spain. Finally, I present my own views regarding the legal value of advance directives in the situation specified above. It is necessary to point out that Act 41/2002 does not limit the application of advance directives to borderline situations of life termination. In fact, the same denomination ('advance directives') covers two different situations. On the one hand, it covers the expression of a given patient's will in relation to an extreme situation of life termination, where the patient is in a state of irreversible unconsciousness, completely dependent on others and being fed and hydrated artificially. On the other hand, it covers those cases where a patient is in a state of reversible unconsciousness that is temporary and can be reversed by applying the required medical treatment. The main conclusion reached in the present article is that advance directives do not have a binding value for doctors in the second situation, a view that is not shared by a good number of scholars, especially in the Common Law tradition. I support that view on the basis of the need to preserve the patient's right to choose her treatment, which is guaranteed by the so-called 'deduced consent'.